Factors affecting employees performance in CTRM Aero Composites Sdn. Bhd. / Muhamad Syafiq Baharudin and Muhammad Amirul Ashraf Kamarudin - Baharudin, Muhamad Syafiq; Kamarudin, Muhammad Amirul Ashraf (Faculty of Business and Management, 2015)
The employee performance is important to company to achieve their goals and target, so our research is focus on the current staff whether they aware of employee performance or not. The primary aim of this study is to explore the main factors that can contribute to the employee performance in CTRM Aero Composites. The data collected through questionnaire from 92 respondents was used to test the proposed hypothesis. The survey questions designed to determine five elements of factor that affecting employee performance which is financial rewards, recognition, working environment and job design. The result reveals the positive relationship of rewards and working environment towards employee performance. Factors and determinants that can help staff in CTRM Aero Composites aware about factors that can affect their performance. There are many other factors which may affect the level of employee performance in CTRM Aero Composites but due to time constraint others are not taken for research. Moreover, the sample was also limited as the only focus was in CTRM Aero Composites staff. The accuracy of the results may be influenced by biases. The results of this study have clearly shown that the independent variables which are education, religion, and subjective norms have a direct and positive impact on the dependent variable that is awareness of employee performance which means the enhancement of one independent variable causes the enhancement in the awareness which is the dependent variable.